Uma proposta de redirecionamento de fluxos de rede usando openflow para migração de aplicações entre nuvens - Moda, Carlos Spinetti (Universidade Federal de São Carlos, 2014)
During the last decade, the advent of large scale processing and the need for rapid modification of computational structures have increased the popularity of Cloud Computing, particularly the Infrastructure as a Service model. Several companies have invested in infrastructure to become providers of this kind of service, whether for general public or only to supply their own business needs. This has increased the number of virtualized datacenters across the world and created a growing interest in interoperability between different providers. However, due to the lack of technology standardization, and to limitations in the current network s architecture, this interoperability is still an issue. Based on this, this research project presents an OpenFlow based network flow redirection architecture to support service continuity during the migration of applications between different IaaS providers. The tests performed show the applicability of the proposed architecture in a real network environment, having control only of the network edges, and without setting up any specific hardware.
Keywords: Redes de computação - protocolos; Computação em nuvem; Redes definidas por software; Infrastructure as a Service (IaaS); OpenFlow; Migração de aplicações; Redirecionamentos de fluxos; IaaS cloud computing; Software defined networks; OpenFlow; Flow redirection; Application migration; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO